Clinicopathological features of 11 Epstein–Barr virus-associated intrahepatic cholangiocarcinoma at a single center in China. Issue 40 (October 2016) - Sun, Ke; Xu, Shaoyan; Wei, Jianfeng; Wang, Bo; Owusu-Ansah, Kwabena Gyabaah; Wang, Weilin; Wu, Jian; Zheng, Shusen
Abstract : Abstract: To date, only 20 cases of Epstein–Barr virus (EBV)-associated intrahepatic cholangiocarcinomas (IHCCs) have been reported in the literature. Pathology records of IHCC from January 1, 2007 to December 31, 2013 were retrieved from our hospital. Clinical information related to EBV-associated IHCC were also obtained, including gender, age at initial diagnosis, tumor size, tumor–node–metastasis stage, and follow-up duration. Surgically resected stage-matched EBV-negative IHCCs with full follow-up were selected for comparison. All liver specimens were fixed in 10% neutral-buffered formalin and paraffin-embedded tissue blocks containing cholangiocarcinoma and nonneoplastic liver tissue. Hematoxylin and eosin-stained sections were present in all cases. Among 329 primary IHCC patients, intranuclear expression of EBV was only found in 11 patients (3.3%), with an age range of 30 to 67 years (mean, 53.2 years; median, 54 years). The group consisted of 4 male and 7 female patients (M:F ratio 1:1.8). Histopathological analysis showed 1 case (9.1%) belonged to the typical lymphoepithelioma-like carcinoma (LELC), primarily composed of undifferentiated tumor cells intimately admixed with abundant lymphoplasmacytic cells. Two cases (18.2%) belonged to the conventional-type IHCCs, showing irregularly shaped neoplastic glands and scattered lymphoplasmacytic infiltration. The remaining 8 cases (72.7%) belonged to the lymphoepithelioma-like cholangiocarcinomas (LELCCs), showing varied glandular differentiation and dense lymphoplasmacytic infiltration. The overall survival of EBV-positive IHCCs was not significantly different from that of EBV-negative IHCCs ( P = 0.512). Our data demonstrate that EBV-associated IHCC is very rare and may be subclassified into 3 different pathological types including LELC, conventional-type IHCC and LELCC on the basis of the tumor cellular differentiation, and host cellular immune responses in the tumors. The etiological, clinical, pathological, and molecular features are needed to be future studied by multicentric efforts in recruiting more EBV-associated IHCC patients.